Mapping the Trajectory of Power Relations in Academia: A Close Reading of Amitabha Bagchi's Above Average. - Mukhopadhyay, Averi (IUP Journal of English Studies, 2020)
Academia represents society at its microcosmic level where students, teachers, administrators, and parents across diverse regions, religions, classes, races, castes, and genders interact with each other. Camaraderie between students and students, faculty and students, faculty and parents, faculty and faculty, and students and administrators develop. This paper argues that the bonhomie existing between the major participants in academia is marked by the interference of power, whereby the one wielding more power by virtue of one's position, class, race, caste, or gender tries to dictate the terms of a particular relationship. A specific code of conduct regarding speech, behavior, dress, thought, writing, love, and life is laid down for all--from professors to students and administrators to parents. The paper calls attention to the fact that embracing fixed roles defined by ideological prejudices, hierarchical divisions, and oppression implies the birth of "power relations" as well as an acceptance of the same. The paper examines, in particular, the trajectory of "power relations" in the light of the course of action defined by power for everyone in academia. However, power in general serves not only to suppress the powerless but is also productive. The paper aims to show how in a specific location as academia as described in Amitabha Bagchi's Above Average, countering power with power creates a proper kind of resistance that blurs the difference between "power" and "resistance" in "power relations".